E-commerce solution for electronic tendering system using secure electronic transaction / Mazlina Abdul Majid - Mazlina , Abdul Majid (2004)
The remarkable growth of companies from day to day is making the business opportunity as a big challenge. To obtain the profit from a business, they have to compete with each other in the fairest way. Tendering process gives companies the same time limit to respond, the same objectives to overcome and with no preferential treatment. In order to provide the reliable, efficient and secure tendering process, this project has been developed with one e-commerce solution called as The Electronic Tendering System (ETS) for Malaysia companies. The system will focus on the website security in terms of secure electronic payment and secure file transfer. The web security protocol that will be implemented is the Secure Electronic Transaction or known as SET. It has been designed to protect credit card transaction on the Internet. Meanwhile for the secure file transfer, the approach that will be used is based on the existing software called as Microsoft Outlook Express. The Outlook has been chosen because it provides the encryption and decryption method to support secure file transfer. ETS provides a secure online infrastructure for front end user to register, read notification of tenders, downloading tender documents, receiving and responding to enquiries, submission of tender proposal and to buy tender document using credit card payment via Internet. Meanwhile for back-end user, ETS can be used to update supplier information, administrator information, update tender notice, awarded tender and read and reply supplier feedbacks. ETS has been developed using Macromedia Dreamweaver MX with support of Microsoft Access 2000 as the database. With the help of ETS, problems with the current tendering process can be overcome.